RADT-09. ROLE OF RADIOTHERAPY IN MANAGEMENT OF PRIMARY SPINAL HIGH GRADE GLIOMA: A SINGLE INSTITUTION RETROSPECTIVE ANALYSIS. (12th November 2021) - Upadhyay, Rituraj; Khose, Swapnil; Pokhylevych, Halyna; Paulino, Arnold dela Cruz; McAleer, Mary Frances; Ghia, Amol; Li, Jing; Yeboa, Debra Nana; Loghin, Monica; Harrison, Rebecca; O'Brien, Barbara; Kamiya-Matsuoka, Carlos; et al.
Abstract: BACKGROUND: Primary spinal high-grade gliomas(S-HGG) are rare, aggressive tumors and radiation therapy(RT) plays a dominant role in the management given their infiltrative nature. We conducted a single-institution retrospective review to study the clinicopathological features and management of S-HGGs. METHODS: Patients with biopsy-proven S-HGG who received RT from 2001-2020 were analyzed for patient, tumor, and treatment characteristics. Kaplan-Meier estimate and Cox proportional hazard regression method were used for survival analyses. RESULTS: Twenty-nine patients were identified with a median age of 25.9 years (range 1-74y). Four patients had gross total resection(GTR) while 25 underwent subtotal resection or biopsy. Nineteen patients had WHO grade 4 tumor. IDH1 mutation and MGMT promoter methylation were analyzed in 14 and four patients respectively; all were IDH wildtype and MGMT-promoter unmethylated. H3K27M mutation was present in five out of 10 patients tested. Twenty-two patients received photon-based radiation and 7 received proton therapy. Median RT dose was 50.4 Gy (range 39.6-54Gy) with 79% receiving >45Gy. 65% patients received concurrent chemotherapy, most commonly temozolomide. Twenty-three (79%) patients had documented recurrence. Overall, 16 patients relapsed locally, 10 relapsed in the brain and 8 developed leptomeningeal disease; only 8(35%) had isolated local relapse. Median OS from diagnosis was 21.3 months and median PFS after RT was 9.7 months. On univariate analysis, age, sex, GTR, grade, RT modality, RT dose and concurrent chemotherapy did not predict for survival. Patients with H3K27M mutation had a poorer median PFS after RT compared to those without the mutation but the difference did not reach statistical significance (p = 0.26). CONCLUSIONS: Although 86% of patients had gross disease at RT and received a lower median RT dose than typically used in cerebral high-grade gliomas, only 55% of patients failed locally. H3K27M mutation may portend worse survival; future studies to improve the therapeutic approach in these patients are warranted.